PruHealth plc: a healthy expansion for discovery? : a healthy expansion for discovery? - Mitchell, Clare; Soicher, Antony ([London] : SAGE, 2016)
PruHealth plc is a 50/50 joint venture formed in late 2004 between Discovery Holdings in South Africa and Prudential plc of the United Kingdom. Whilst PruHealth had the backing of two very substantial shareholders, it is generally accepted that joint ventures are notoriously difficult to manage. This text explains how PruHealth set about challenging this notion.
Originally Published in: Townsend, S., & Mosala, T. (2006). PruHealth plc: A Healthy Expansion for Discovery? WBS-2006-8. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; PruHealth (Firm); Joint ventures -- Case studies; Joint ventures -- Management -- Case studies